Assessment of the Prognostic Effect of Blood Urea Nitrogen to Serum Albumin Ratio in Patients with Fournier’s Gangrene in a Referral Center - Allameh, Farzad; Montazeri, Saeed; Shahabi, Vahid; Hojjati, Seyyed Ali; Alinejad Khorram, Amir; Razzaghi, Zahra; Dadkhahfar, Sahar (Urology Journal, 2021)
Purpose: To assess the prognostic effect of blood urea nitrogen to serum albumin ratio in patients with Fournier’s gangrene (FG) in a referral center in order to reduce the mortality of FG patients. Materials and Methods: Patients with FG were admitted and enrolled consecutively in this study from March 2008 to April 2020. Statistical analysis was done to evaluate the differences between the two groups and to identify the best cutoff value to predict mortality and the need for intensive care. Results: Of all 114 patients, 46 patients (40.35%) died in the course of hospitalization and 40 entered the study. No variable manifested a notable difference except for the BUN to albumin ratio, which was significantly different (P-value = 0.045). The ratio of BUN to albumin was not associated with any other variables and was independently a predictor of death in FG patients. Conclusion: The ratio of BUN to albumin was significantly different among deceased and survived patients with FG. Therefore, more studies with a larger sample size are still needed to access this parameter properly.